2005
DOI: 10.1212/01.wnl.0000187075.81589.fd
|View full text |Cite
|
Sign up to set email alerts
|

BDNF genetic variants are associated with onset age of familial Parkinson disease: Gene PD Study

Abstract: When more really means more: WGS standards and quality control Next-generation sequencing (NGS) is reshaping the landscape of modern genetic diagnostic laboratories and their operational standards. NGS is gradually replacing the single-gene Sanger sequencing with targeted multigene panel-based resequencing for genes with variants implicated in any number of common diseases, from cardiovascular or neurological disorders to cancers or drug treatment response. Further advances in technology are positioning whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
4
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 12 publications
(11 reference statements)
0
27
4
1
Order By: Relevance
“…Also, according to our data, the G196A polymorphism did not seem to modify motor and nonmotor clinical features and treatment complications in PD patients. It did not influence age of onset and was uniformly distributed among sporadic and familial cases, which is in contrast to the report by Karamohamed et al [27] which showed the G196A polymorphism was associated with an older onset of the disease. Similar to our study, a meta-analysis did not support the hypothesis that this variation was a risk factor for idiopathic PD [11].…”
Section: Discussioncontrasting
confidence: 99%
“…Also, according to our data, the G196A polymorphism did not seem to modify motor and nonmotor clinical features and treatment complications in PD patients. It did not influence age of onset and was uniformly distributed among sporadic and familial cases, which is in contrast to the report by Karamohamed et al [27] which showed the G196A polymorphism was associated with an older onset of the disease. Similar to our study, a meta-analysis did not support the hypothesis that this variation was a risk factor for idiopathic PD [11].…”
Section: Discussioncontrasting
confidence: 99%
“…These results suggest that the genotype and allele frequencies of this polymorphism differ between ethnics. Homozygosity M/M for the BDNF V66M variant associated with a 5.3-year older onset age was shown recently in a large cohort of familiar PD [Karamohamed et al, 2005]. However, in the present study, the onset age of Taiwanese PD is not influenced by BDNF V66M.…”
Section: Discussioncontrasting
confidence: 65%
“…However, these studies are sparse and have provided conflicting results. The BDNF Met/Met genotype was, for instance, associated with a higher risk of developing dyskinesias earlier in the course of treatment with dopaminergic agents (Foltynie et al, 2009) and an older age of onset (Karamohamed et al, 2005), whereas other studies were unable to find any association with clinical characteristics, including dyskinesias or age at onset (Gao et al, 2010;Karakasis et al, 2011). As these studies used different outcome measures, have individually not been replicated, and were all cross sectional, it is difficult to establish the exact role, if any, of BDNF in explaining the clinical variability of PD.…”
Section: Introductionmentioning
confidence: 99%